Maxwell Anderson papers - Anderson, Maxwell, 1888-1959.
Correspondence between Anderson and Harold Monro, plays, screenplays, drafts, and galleys.
Playwright.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Anderson, Maxwell, -- 1888-1959 -- Correspondence; Monro, Harold, -- 1879-1932 -- Correspondence; Drama -- Stories, plots, etc; Motion picture plays, American; Dramatists